Political thinkers : from Socrates to the present - Boucher, David, 1951-; Kelly, P. J. (Paul Joseph); Oxford University Press (Oxford ; New York : Oxford University Press, 2009)
An introduction to the history of Western political thought written by scholars from four continents. This collection provides an overview of the canon of great theorists from Socrates and the Sophists to contemporary thinkers such as Habermas and Foucault.
Contents r t t t t t t r r r r t t t t t t t t t t t t r r r r r r r r t t t t t
Includes bibliographical references and index.
Keywords: Political science -- History; Political science -- Philosophy